C.B. Comstock papers - Comstock, C. B. (Cyrus Ballou), 1831-1910.
Correspondence, memoranda, diaries, memoirs, reports, notebooks, orders, memoirs, sketches, and other papers primarily concerning Comstock's Civil War service as chief engineer of the Army of the Potomac.
Topics include the siege of Vicksburg, Miss.; the capture of Fort Fisher, N.C.; the fords on the Rapidan and Rappahannock rivers, Va.; the defenses at Aquia Creek, Va. and Harpers Ferry, W. Va.; Ulysses S. Grant's resignation as U.S. secretary of war under Andrew Johnson; James K. Polk's 1847 annual message to Congress concerning the Mexican War; Comstock's service as president of the U.S. Mississippi River Commission (1884) including improvement of the Mississippi River; the ancestry of Jesse Root Grant; and William Petit Trowbridge.
Correspondents include Henry Martyn Adams, B.S. Alexander, Daniel Butterfield, James Buchanan Eads, Ulysses S. Grant, H.W. Halleck, A.A. Humphreys, George Gordon Meade, David D. Porter, John McAllister Schofield, Philip Henry Sheridan, William T. Sherman, Daniel Edgar Sickles, E.D. Townsend, Seth Williams, and Horatio Gouverneur Wright.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
U.S. Army officer and engineer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Henry Martyn, -- 1844-1909 -- Correspondence; Alexander, B. S. -- 1819-1878 -- Correspondence; Butterfield, Daniel, -- 1831-1901 -- Correspondence; Eads, James Buchanan, -- 1820-1887 -- Correspondence; Grant, Jesse Root, -- 1794-1873 -- Correspondence; Grant, Jesse Root, -- 1794-1873 -- Family; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Resignation from office; Halleck, H. W. -- 1815-1872 -- Correspondence; Humphreys, A. A. -- 1810-1883 -- Correspondence; Meade, George Gordon, -- 1815-1872 -- Correspondence; Polk, James K. -- 1795-1849.; Porter, David D. -- 1813-1891 -- Correspondence; Schofield, John McAllister, -- 1831-1906 -- Correspondence; Sheridan, Philip Henry, -- 1831-1888 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Sickles, Daniel Edgar, -- 1819-1914 -- Correspondence; Townsend, E. D. -- 1817-1893 -- Correspondence; Trowbridge, William Pettit, -- 1828-1892.; Williams, Seth, -- 1822-1866 -- Correspondence; Wright, Horatio Gouverneur, -- 1820-1899 -- Correspondence; United States. -- Army of the Potomac; United States. -- Mississippi River Commission; Fords (Stream crossings) -- Virginia -- Rapidan River; Fords (Stream crossings) -- Virginia -- Rappahannock River; Fortification -- North Carolina; Mexican War, 1846-1848.; Presidents -- United States -- Messages; Aquia Creek (Va.) -- History; Fort Fisher (N.C. : Fort) -- Capture, 1865.; Harpers Ferry (W. Va.) -- History; Mississippi -- History -- Civil War, 1861-1865.; Mississippi River -- Navigation; North Carolina -- History -- Civil War, 1861-1865.; Rapidan River (Va.); Rappahannock River (Va.); United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Engineering and construction; Vicksburg (Miss.) -- History -- Civil War, 1861-1865.; Vicksburg (Miss.) -- History -- Siege, 1863.; Virginia -- History -- Civil War, 1861-1865.; West Virginia -- History -- Civil War, 1861-1865.; Army officers; Engineers